Peningkatan Pendaftaran Siswa Melalui Strategi Pengembangan Website dan Optimalisasi PPDB Online - Syafiih, M.; Syauqillah, M. Ilham Zidni; Pimbiriri, M. Alif Oleo (Jurnal Aplikasi Teknologi Informasi dan Manajemen (JATIM), 2024)
Yayasan Tarbiyatul Islamiyah faces challenges in the student enrollment process due to the absence of a website and an online New Student Enrollment (PPDB) system. This situation results in manual administrative processes, leading to low efficiency and a high risk of data recording errors. This study aims to develop an online PPDB system using the Waterfall method, with stages including needs analysis, design, implementation, testing, and maintenance. The system is developed using PHP and MySQL to ensure structured and efficient data management. The results indicate that the online PPDB system can accelerate the enrollment process, reduce errors, and expand information access for prospective students and parents. This implementation not only enhances the foundation's appeal but also serves as a reference for other educational institutions adopting similar technology. In conclusion, this system development successfully improves the efficiency and accessibility of student enrollment at Yayasan Tarbiyatul Islamiyah.